2012
DOI: 10.1002/bies.201200146
|View full text |Cite
|
Sign up to set email alerts
|

Hox transcriptional specificity despite a single class of cofactors: Are flexible interaction modes the key?

Abstract: Editor's suggested further reading in BioEssays ftz Evolution: Findings, hypotheses and speculations (response to DOI 10.1002/bies.201100019) AbstractOn the border of the homeotic function: Re‐evaluating the controversial role of cofactor‐recruiting motifs AbstractControl of DNA replication: A new facet of Hox proteins? AbstractClassification of sequence signatures: a guide to Hox protein function Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Paralog-specific repression is mediated by a region in the Hoxc9 N-terminus that has no appreciable impact on DNA-binding. Such specific regulatory output might be mediated by the direct recruitment of specific co-regulator(s) or by forming a structurally distinct complex with the TALE cofactors that recruits specific co-regulators (see below and [25]).…”
Section: Flavors Of Hox-tale Target Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Paralog-specific repression is mediated by a region in the Hoxc9 N-terminus that has no appreciable impact on DNA-binding. Such specific regulatory output might be mediated by the direct recruitment of specific co-regulator(s) or by forming a structurally distinct complex with the TALE cofactors that recruits specific co-regulators (see below and [25]).…”
Section: Flavors Of Hox-tale Target Genesmentioning
confidence: 99%
“…Importantly, the W motif is not the only PBC interaction motif in Hox proteins, and it is even dispensable for some PBC-dependent Hox functions (see [25] for review). The existence of alternative interaction modes between Hox and PBC proteins was definitively established with the identification of novel PBC interaction motifs in several Drosophila Hox proteins [4547].…”
Section: Flexibility In Hox-tale Interaction Properties and The Recogmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them converge to support the predominant role of a unique motif of Hox proteins, called hexapeptide (HX), in making strong interactions with the PBC partner ( Figure 1A). However, these results are in contradiction with the observation that this conserved motif is dispensable in several Hox proteins for interaction and function with TALE cofactors in vivo (Merabet and Hudry, 2013). It is tempting to postulate that the distinct regulatory activities of Hox/TALE complexes rely on their interaction via different protein motifs.…”
mentioning
confidence: 56%
“…It has been previously suggested that the arrangement of Hox-PBC-HMP binding sites may contribute to the activity of Hox-regulated CRM independent of paralog specificity [144]. To test this idea, we recently altered the configuration of Hox sites within the DCRE by swapping them with the Exd/Hth/Hox site found within the RhoA CRM [70].…”
Section: Case Study: the Distal-less Conserved Regulatory Elementmentioning
confidence: 99%